1994
DOI: 10.3109/00365529409092497
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional Small-Intestinal Permeability in the Rat to Some Common Marker Molecules in vitro

Abstract: The intestinal epithelial barrier is more permeable in the outward than in the inward direction, and regional permeability differences exist in a size-dependent fashion. The results suggest two passage routes, one for the smallest molecule, mannitol, and a second for the larger markers in the present size range, both apparently different from the route for macromolecules such as intact proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…17) In contrast, Pantzar et al reported that the net rate of fluid-phase transcytosis of [ 3 H]inulin across cultured MDCK epithelial cells is approximately equal in both directions, even though the basolateral endocytotic rate is 6-fold greater than the apical rate. 18) In our study, we observed that mucosato-serosal and serosal-to-mucosal fluxes of laminaran are nonlinear transport on the concentration of the laminaran in the donor chamber. These findings are consistent with transport in both fluxes occurring as a result of membrane traffic, and paracellular permeation, or a combination of both processes.…”
Section: Discussionmentioning
confidence: 79%
“…17) In contrast, Pantzar et al reported that the net rate of fluid-phase transcytosis of [ 3 H]inulin across cultured MDCK epithelial cells is approximately equal in both directions, even though the basolateral endocytotic rate is 6-fold greater than the apical rate. 18) In our study, we observed that mucosato-serosal and serosal-to-mucosal fluxes of laminaran are nonlinear transport on the concentration of the laminaran in the donor chamber. These findings are consistent with transport in both fluxes occurring as a result of membrane traffic, and paracellular permeation, or a combination of both processes.…”
Section: Discussionmentioning
confidence: 79%
“…In addition, it is also likely that permeation of marker molecules is higher in the blood to lumen direction than in the opposite direction. Strong support for this view comes from in vitro studies on both the small and large bowel showing a much higher permeation of nearly all commonly used marker molecules in the serosa to mucosa direction than in the mucosa to serosa direction [36,37] .…”
Section: Discussionmentioning
confidence: 88%
“…Using primary cultures of canine proximal tubular renal epithelial cells, Goligorsky et al reported that the flux of LY, which is generally regarded as a marker of fluid-phase endocytosis, was 3-fold greater in the basal-to-apical direction than in the apical-to-basal direction [26]. In contrast, Pantzar et al reported that the net rate of fluid-phase transcytosis of [ 3 H] inulin across cultured MDCK epithelial cells was approximately equal in both directions, even though the basolateral endocytotic rate was 6-fold greater than the apical rate [27]. In our study, we observed that the mucosa-to-serosal and serosal-to-mucosal fluxes of FD-4 involve nonlinear transport that is dependent on the concentration of FD-4 in the donor chamber.…”
Section: Discussionmentioning
confidence: 92%